Performance of a prototype RICH detector using hybrid photo-diodes - Albrecht, E; Barber, G; Bibby, J; Brook, N; Duane, A; French, M; Gibson, V; Giles, R; Halley, A; Harnew, N; John, M; Miller, D; et al. (Elsevier, 2001)
A prototype Ring-Imaging Cherenkov detector has been operated in a charged particle test beam. Cherenkov photons are imaged onto a plane of hybrid photo-diode detectors. The geometrical arrangement of the prototype and data-taking conditions are described. An analysis of the detector performance, using silica aerogel, air and C4F10 gas radiators, is presented. The photon yields and observed Cherenkov angle resolutions are found to be in good agreement with Monte Carlo simulation and satisfy the requirements of the RICH 1 detector in the LHCb experiment.